Boosting Autobiographical Memory and the Sense of Identity of Alzheimer Patients Through Repeated Reminiscence Workshops? - Platel, Hervé; Eustache, Marie-Loup; Coppalle, Renaud; Viard, Armelle; Eustache, Francis; Groussard, Mathilde; Desgranges, Béatrice (Frontiers in Psychology, 2021)
Despite severe amnesia, some studies showed that Alzheimer Disease (AD) patients with moderate to severe dementia keep a consistent, but impoverished representation of themselves, showing preservation of the sense of identity even at severe stages of the illness. Some studies suggest that listening to music can facilitate the reminiscence of autobiographical memories and that stimulating autobiographical memory would be relevant to support the self of these patients. Consequently, we hypothesized that repeated participation to reminiscence workshops, using excerpts of familiar songs as prompts would participate to the enrichment of autobiographical memories, self-representation and sense of identity. We included a group of 20 AD patients with severe dementia residing in nursing homes. Their performances were compared to a control group of 20 matched (age, education, mood) healthy residents living in the same institutions. The experiment was conducted in three phases over a two-week period. On phase 1, an individual assessment of sense of identity was proposed to each participant. On phase 2, participants joined musical reminiscence workshops (6 sessions over two weeks for AD patients and 3 sessions over a week for controls). During the third phase (12 days after the first assessment), individual evaluation of autobiographical memory and a second assessment of sense of identity were proposed. Our results showed that, despite their massive amnesia syndrome, autobiographical memories of AD reached at the end of the two weeks the number and quality of those of matched controls. Moreover, we confirmed a continuity of self-representation in AD patients with a stable profile of the answers between the first and second individual assessments of sense of identity. However, the increase in number and episodic quality of autobiographical memories was not accompanied by an enrichment of the sense of identity. In a complementary study, new patients participated in the same paradigm, but using movie extracts as prompts, and showed very similar effects. We discuss all of these results with regard to the literature showing the significant impact of repetition on the reactivation of memory traces even in very amnestic AD patients at severe stages of the disease.